(untitled) (Research, Society and Development, 2022)
Objective: To provide the dentist with an objective analysis of the radiographic methods useful to evaluate the relationship between the roots of the maxillary posterior teeth and the maxillary sinus. Methodology: We carried out an integrative review of the literature, we used 23 articles published in English from the last twelve years, within the PubMed database and a manual search aggregate. Results: After using our inclusion and exclusion criteria, a total of 23 articles were chosen for the elaboration of this literary review and one book. Discussion: During certain dental procedures in the upper jaw there is a risk of injuring the maxillary sinus, it is important to radiographically evaluate the patient before performing any procedure. Although panoramic radiographs are inexpensive and offer us the necessary visualization to detect the relationship of the upper posterior teeth with the maxillary sinus, there are cases in which these images are not totally accurate and a CBCT study is required. Conclusion: The panoramic image is useful for the analysis of the roots of the teeth and the maxillary sinus as long as the teeth do not move towards the sinus, but the CBCT image is incomparable in terms of its accuracy in the position of the different structures. However, for the final decision, is important factors such as: dental piece to be evaluated, sex and age, the price of each study, radiation dose and the need depending on each case.